Simulation on the Effect of Bottle Wall Thickness Distribution using Blow Moulding Technique - Suraya, Sulaiman; M. D., Azman; Fatchurrohman, Nanang; Abdul Aziz, Jaafar; A. R., Yusoff (IOP Publishing, 2016)
The aims of this study are to assess the deformation behavior of a polymeric material during a blow moulding process. Transient computations of two dimensional model of a PP bottle were performed using ANSYS Polyflow computer code to predict the wall thickness distribution at four different parison's diameter; 8mm, 10mm, 18mm, and 20mm. Effects on the final wall thickness diameter and time step are studied. The simulated data shows that the inflation performance degrades with increasing parison diameter. It is concluded that the blow moulding process using 10mm parison successfully meet the product processing requirements. Factors that contribute to the variation in deformation behaviour of the plastic during the manufacturing process are discussed.